The Influence of Online Loans on Consumer Behavior of the Community in Dendang Sub-District - Abidin, Zaenal; Saputra, Ahmad Edi; Pilisia, Ade Elfhina (Zabags International Journal of Economy, 2025)
The rise of digital technology has significantly reshaped consumption patterns, particularly through the widespread use of online loan services that allow individuals to meet lifestyle demands beyond basic needs. This study investigates the influence of online loans on consumerist behavior among residents of Dendang Sub-District. Using a quantitative approach with a causality design, data were collected from 91 respondents aged 20–29 through questionnaires and analyzed using descriptive statistics, classical assumption tests, and simple linear regression. The results showed that online loan applications had a significant effect on consumptive behavior with a contribution of 8.4%, while 91.6% were influenced by other factors. This is evidenced by a t-calculated value of 2.859 which is greater than the t-table of 1.662, and a significance value of 0.005 which is smaller. The results indicate that online loan usage significantly affects consumerist behavior, with a high tendency toward impulsive and non-essential spending. The regression analysis confirms a positive and statistically significant relationship between the independent and dependent variables. This finding highlights the role of fintech platforms in facilitating immediate gratification and fostering financially unsustainable habits among young adults. The study contributes empirical evidence to the discourse on digital consumption and offers valuable insights for policymakers and practitioners seeking to mitigate the adverse effects of online lending on household financial stability.